Creating walking led transit stations for women in Malaysia / Yong Adilah Shamsul Harumain, Nur Farhana Azmi and Suhaini Yusoff - Shamsul Harumain, Yong Adilah; Azmi, Nur Farhana; Yusoff, Suhaini (Universiti Teknologi MARA, Perak, 2020)
Transit stations are generally well known as nodes of spaces where percentage of people walking are relatively high. The issue is do more planning is actually given to create walkability. Creating walking led transit stations involves planning of walking distance, providing facilities like pathways, toilets, seating and lighting. On the other hand, creating walking led transit station for women uncover a new epitome. Walking becomes one of the most important forms of mobility for women in developing countries nowadays. Encouraging women to use public transportation is not just about another effort to promote the use of public transportation but also another great endeavour to reduce numbers of traffic on the road. This also means, creating an effort to control accidents rate, reducing carbon emission, improving health and eventually, developing the quality of life. Hence, in this paper, we sought first to find out the factors that motivate women to walk at transit stations in Malaysia. A questionnaire survey with 562 female user of Light Railway Transit (LRT) was conducted at LRT stations along Kelana Jaya Line. Both built and non-built environment characteristics, particularly distance, safety and facilities were found as factors that are consistently associated with women walkability. With these findings, the paper highlights the criteria which are needed to create and make betterment of transit stations not just for women but also for walkability in general.